Rethinking Nature Es Baluard Museu d'Art Contemporani de Palma - (:unkn) unknown (My University, 2026)
Rethinking Nature Es Baluard Museu d'Art Contemporani de Palma Organized by: Maritima Art Project Founder and Director Elena Posokhova Moderated by: Laurine Wagner “The Mediterranean Topos” Monday, June 7, 2021 at 8 PM